Food for feeling healthy - Ballard, Carol (Oxford : Heinemann, 2006)
Discusses the importance of making healthy food chooses, exploring the reason why people eat, lookingat what is in food, exploring food labels, and including recipes and a one-week menu.
Keywords: Nutrition; Nutrition -- Juvenile literaure